Knowledge on voluntary medical male circumcision in a low uptake setting in northern Uganda - Barbara Marjorie Nanteza; David Serwadda; Edward Nelson Kankaka; Grace Bua Mongo; Ronald Gray; Frederick Edward Makumbi (BMC, 2018)
Abstract Background Free VMMC services have been available in Uganda since 2010. However, uptake in Northern Uganda remains disproportionately low. We aimed to determine if this is due to men's insufficient knowledge on VMMC, and if women's knowledge on VMMC has any association with VMMC status of their male sexual partners. Methods In this cross sectional study, participants were asked their circumcision status (or that of their male sexual partner for female respondents) and presented with 14 questions on VMMC benefits, procedure, risk, and misconceptions. Chi square tests or fisher exact tests were used to compare circumcision prevalence among those who gave correct responses versus those who failed to and if p < 0.05, the comparison groups were balanced with propensity score weights in modified poisson models to estimate prevalence ratios, PR. Results A total of 396 men and 50 women were included in the analyses. Circumcision was 42% less prevalent among males who failed to reject the misconception that VMMC reduces sexual performance (PR = 0.58, 95% CI 0.38-0.89, p = 0.012), and less prevalent among male sexual partners of females who failed to reject the same misconception (PR = 0.22, 95% CI = 0.07-0.76, p = 0.016). Circumcision was also 35% less prevalent among male respondents who failed to reject the misconception that VMMC increases a man's desire for more sexual partners i.e. promiscuity (PR = 0.65, 95% CI = 0.46-0.92, p = 0.014). Conclusion Misconceptions regarding change in sexual drive or performance were associated with circumcision status in this population, while knowledge of VMMC benefits, risks and procedure was not.